Population Genomics of Microbial Biostalactites: Non-recombinogenic Genome Islands and Microdiversification by Transposons - Burkartová, Kateřina; Dresler, Jiří; Rídl, Jakub; Falteisek, Lukáš (Frontiers in Microbiology, 2022)
Intrapopulation genetic variability in prokaryotes is receiving increasing attention thanks to improving sequencing methods; however, the ability to distinguish intrapopulation variability from species clusters or initial stages of gene flow barrier development remains insufficient. To overcome this limitation, we took advantage of the lifestyle of Ferrovum myxofaciens, a species that may represent 99% of prokaryotic microbiome of biostalactites growing at acid mine drainage springs. We gained four complete and one draft metagenome-assembled F. myxofaciens genomes using Oxford Nanopore and Illumina sequencing and mapped the reads from each sample on the reference genomes to assess the intrapopulation variability. We observed two phenomena associated with intrapopulation variability: hypervariable regions affected by mobilome expansion called “scrapyards,” and variability in gene disruptions caused by transposons within each population. Both phenomena were previously described in prokaryotes. However, we present here for the first time scrapyard regression and the development of a new one. Nearly complete loss of intrapopulation short sequence variability in the old scrapyard and high variability in the new one suggest that localized gene flow suppression is necessary for scrapyard formation. Concerning the variable gene disruptions, up to 9 out of 41 occurrences per sample were located in highly conserved diguanylate cyclases/phosphodiesterases. We propose that microdiversification of life strategies may be an adaptive outcome of random diguanylate cyclase elimination. The mine biostalactites thus proved as a unique model system for describing genomic intrapopulation processes, as they offer easily sampleable units enriched in a single microbial species.